Meningkatkan Minat Belajar dan Kreativitas Siswa Serta Menanamkan Rasa Peduli Terhadap Lingkungan di SD Karanganyar 3 - Ubaidillah, Mohammad; Puspito, Agung Nugroho; Suud, Hasbi Mubarak; Mubarakah, Lailatul; Kirana, Zakiyah Galuh Pusphita Candra; Febriyanti, Dwi Aidil; Putri, Revita Salsabila; Nayyiroh, Dini Anjum Milatin; Siswanto, Siti Mazzhidha Rhaumi Novia; Sari, Sasmita (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
This research was initiated due to students facing challenges in demonstrating environmental care and showing a lack of interest in the learning process. The issue stemmed from teachers delivering material solely through textbooks, focusing only on theoretical aspects, and dominating the learning environment. To address this concern, the proposed solution involves incorporating practical applications of the material in a phased manner. The objective of this study is to assess the enhancement of both teacher and student engagement, the learning outcomes derived from the direct application of material, and student attitudes toward caring for the school environment and the community. Employing the classroom action research method, the study is structured in two cycles, with observation sheets for student activities and tests serving as the primary instruments. The data analysis combines descriptive, qualitative, and quantitative approaches. The findings indicate noticeable improvements in learning outcomes, student activities, and student responses with each successive cycle.